Evaluation of Some Management Procedures for Controlling Broodiness in Turkey and Muscovy Duck - Mohamed, Radi Ali; Mousa-Balabel, Tarek; Elbassiouny, Ahmed (Journal of Advanced Veterinary Research, 2013)
The objective of this study was to evaluate pens switching, closing nest boxes after egg laying and nest boxes switching inside the same pen as management procedures for controlling broodiness in turkey and Muscovy duck breeders and their role in circulating prolactin. Black bronze turkey (n.= 350) and Muscovy duck (n.= 700) were randomly selected and housed on deep litter. The results showed a significant (P ≤ 0.05) increase in egg production in turkey and Muscovy duck breeders in response to pens switching and closing nest boxes after end of egg laying. While, there was no significant (P > 0.05) difference in egg production in response to switching of nest boxes in turkey hens but a significant (P ≤ 0.05) result was found in Muscovy ducks. On the other hand, there were significant (P ≤ 0.05) decreases in circulating prolactin level and broodiness in both turkey and Muscovy duck breeders in response to pen switching, closing nest boxes after egg laying and nest boxes switching. In conclusion, application of these management procedures was associated with increased egg production while decreased expression of broodiness (incubation behaviour) and circulating prolactin in turkey hens and Muscovy ducks.